Hubungan Stres Akademik, Kualitas Tidur, dan Rasa Kehadiran di Kampus terhadap Gejala Depresi pada Mahasiswa Prodi Penjaskesrek Universitas PGRI Sumenep - Moh. Junaidi; Winda Nuraisyah; Dian Helaprahara (MAN Insan Cendekia Jambi, 2026)
The purpose of this final project research is to analyse the relationship between academic stress, sleep quality, sense of belonging on campus, and symptoms of depression among students of the Physical Education, Health, and Recreation Study Programme at PGRI University Sumenep. Furthermore, this study employs a quantitative approach with a correlational design and utilises Structural Equation Modelling analysis through Partial Least Squares. Data collection was conducted on 250 students using stratified random sampling techniques. The results indicate that academic stress has a positive effect on depressive symptoms, while sleep quality and campus belonging act as mediators, thereby mitigating the negative impact of stress on depressive symptoms. The implication of these findings is that higher stress tends to exacerbate symptoms of depression, while sleep quality and social attachment to campus are able to mediate its impact. The principles of stress management are also discussed, emphasising the importance of improving sleep quality and social attachment to campus in order to reduce the strong negative impact of stress on symptoms of depression.